If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -7y + 1 = 11 Reorder the terms: 1 + 5y + -7y = 11 Combine like terms: 5y + -7y = -2y 1 + -2y = 11 Solving 1 + -2y = 11 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2y = 11 + -1 Combine like terms: 1 + -1 = 0 0 + -2y = 11 + -1 -2y = 11 + -1 Combine like terms: 11 + -1 = 10 -2y = 10 Divide each side by '-2'. y = -5 Simplifying y = -5
| 2x+56x+342x-133x= | | 2n+6=16 | | 2x+56x= | | 5r-7r=16 | | 5x-3=x^2-2x+x+6 | | x^2+x-3=0 | | 12m=17 | | (13b-1)-4(3b+3)=-4 | | 6x+5x+3+7=6x+4+4x | | 7*x+9*x=52 | | 35x*4=0 | | 8(b+4)=40 | | 14x-(9x-7)=11+(-3+62) | | (3*x)+5=53 | | 2x(9-7x)=0 | | k*p=16 | | h*h+g*g=64 | | s+5=7 | | s*s-12s+12=0 | | 3+27x+15=5x+18+22x | | 0.75*18+0.25*x=17 | | 0.25x^2-5x=10 | | 4p+2q=28 | | 1+a=b-1 | | 8n-30=42 | | 4p+3q=26 | | (x+-2)(x+-2)=-25 | | 400=16t | | 12x^2+25x-7=0 | | 7m+7n= | | 2x+4x+3y= | | 79-4x=23x+19 |